Pemaknaan Khalayak Digital Terhadap Homoseksualitas Dalam Serial A Tale of Thousand Stars - Rahma Az Zahra Laksmitha; Nurul Hasfi; S. Rouli Manalu (Interaksi Online, 2023)
This research is based on the emergence of enthusiasm among Generation Z of Indonesia for serial Thai films that raise the issue of homosexuality, while the majority of Indonesian people themselves still often debate the issue of homosexuality. In Indonesia, one of the Thai series with the theme of homosexuality that quite popular is A Tale of Thousand Stars which reach an average number of Indonesian viewers of 1,331,126 viewers. The aim of this research is to see the public's interpretation of homosexuality in the series A Tale of Thousand Stars. This study uses Stuart Hall's reception analysis as a research analysis method to answer the research objectives. The findings of the research conducted on six male and female informants with different ages, religions and cultural backgrounds indicate that various interpretations of homosexuality in A Tale of Thousand Stars the series are obtained which are more inclined to a dominant position. Homosexuality which is shown through aspects of expression of sexual orientation, identity formation, and physical intimacy can be easily accepted by informants because the six informants are Generation Z who use the internet and social media which easily provide access to information related to homosexuality. In addition, there were 2 informants who had friends who were part of a homosexual group, and there was also one informant who was a homosexual. With these various meanings, it means that there has been a shift in meaning towards homosexuality which is exhibited in A Tale of Thousand Stars the series.